Association of type 2 diabetes mellitus with the interaction between low‐density lipoprotein receptor‐related protein 5 (LRP5) polymorphisms and overweight and obesity in rural Chinese adults: 中国农村成人中低密度脂蛋白受体相关蛋白5(LRP5)基因多态性和超重及肥胖的交互作用与2型糖尿病的关联研究. (2nd March 2017) - Zhang, Lu; Wang, Jinjin; Zhang, Ming; Wang, Guo'an; Shen, Yanxia; Wu, Dongting; Wang, Chongjian; Li, Linlin; Ren, Yongcheng; Wang, Bingyuan; Zhang, Hongyan; Yang, Xiangyu; et al.
Abstract: Background: Low‐density lipoprotein receptor‐related protein 5 (LRP5) plays an important role in glucose and cholesterol metabolism. The present cohort study evaluated associations of LRP5 variants with the incidence of type 2 diabetes mellitus (T2DM) in a rural adult Chinese population. Methods: In all, 7751 subjects aged ≥18 years without T2DM underwent genotyping at baseline; 6326 subjects (81.62%) were followed‐up, and 5511 with a clear disease outcome were eligible for analysis. The same questionnaire was administered and the same anthropometric and blood biochemical examinations were performed at baseline and follow‐up. Association analysis was performed for five single nucleotide polymorphisms and haplotypes of LRP5 . Results: Cox proportional hazards testing of three different genetic models found no significant association between T2DM and LRP5 after adjusting for potential risk factors ( P  > 0.05). However, the incidence of T2DM in subjects with LRP5 mutational genotypes was higher in the overweight/obese than normal weight population. Under the dominant model, the risk of T2DM was increased with an interaction between rs11228303 and the waist‐to‐height ratio adjusted for baseline age, sex, and family history of T2DM (synergy index [SI] = 4.172; 95% confidence interval [CI] 1.014–17.166)], and body mass index (SI = 3.237; 95% CI 1.102–9.509). Furthermore, the A allele of rs3758644 was related to decreased fasting plasma insulin and homeostatic model assessment of β‐cell function levels, whereas the T allele of rs12363572 was related to increased high‐density lipoprotein cholesterol levels in new‐onset diabetes patients ( P  < 0.05). Conclusions: The risk of T2DM may be associated with interactions between the LRP5 gene and overweight and obesity. Polymorphisms of LRP5 are related to β‐cell function and lipid metabolism. Abstract : Highlights This study provides important evidence that the interaction between LRP5 and environmental factors may affect the risk of type 2 diabetes mellitus (T2DM). The risk of T2DM may be increased with by an interaction between LRP5 and overweight and obesity. Furthermore, LRP5 polymorphisms are related β‐cell function and lipid metabolism.